The Importance of Student Development in Selecting College Majors According to Their Interests and Talents at Man 5 Tasikmalaya - Nurnisaa binti Abdullah Suhaimi; Kalfin Kalfin; Moch Panji Agung Saputra (Research Collaboration Community (RCC), 2024)
Choosing a college major is one of the important stages that students at the upper secondary level must go through. The decision to choose the right college major will greatly determine the future and success of students after graduation and they will not face difficulties during the study process. MAN 5 Tasikmalaya is one of the leading madrasah aliyah in Tasikmalaya which has experience in developing and guiding its students. As a school that has quite good quality, MAN 5 Tasikmalaya is required to provide maximum guidance to students in choosing college majors according to their interests and talents. It is hoped that MAN 5 Tasikmalaya students can discover their academic interests and talents from an early age so that they can make a decision on the right college major. appropriate. Good coaching will certainly be very beneficial for the future of students. This research aims to analyze the guidance for selecting college majors carried out at MAN 5 Tasikmalaya in helping students determine study programs that suit their interests and talents. The research results show that the coaching carried out by MAN 5 Tasikmalaya is quite effective in helping students determine their college major according to their interests and talents. However, the quality and quantity of coaching needs to continue to be improved by involving various internal and external parties at the school. The more optimal the coaching is, the more MAN 5 Tasikmalaya graduates will choose the right college major based on their interests and talents, so that they can achieve success in the future.